The parables of Jesus - Buttrick, George Arthur, 1892-1980 (Grand Rapids, MI Baker, 1973)
Includes bibliographical references and indexes.
Originally published 1928 by Harper & Brothers
Keywords: Bible. N.T. Parables -- criticism, interpretation, etc